2017
DOI: 10.1542/peds.2016-2509
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Pregnancy and Child ADHD

Abstract: BACKGROUND AND OBJECTIVE:There is a well-documented association between maternal smoking during pregnancy and offspring attention-deficit/hyperactivity disorder (ADHD). The degree to which this reflects causal intrauterine effects or is due to unmeasured confounding is not clear. We sought to compare the association between maternal smoking during pregnancy and offspring ADHD with the associations with paternal smoking, grandmother's smoking when pregnant with mother, and maternal smoking in previous pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
86
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 30 publications
9
86
0
3
Order By: Relevance
“…Keyes et al 45 found that there was no association between paternal smoking and offspring ADHD after adjustment for several covariates. In contrast, Gustavson et al 36 reported that paternal smoking increased the risk of ADHD by 1.23 times. We searched the databases, and 7 related studies were included for further analysis.…”
Section: Figurementioning
confidence: 91%
See 3 more Smart Citations
“…Keyes et al 45 found that there was no association between paternal smoking and offspring ADHD after adjustment for several covariates. In contrast, Gustavson et al 36 reported that paternal smoking increased the risk of ADHD by 1.23 times. We searched the databases, and 7 related studies were included for further analysis.…”
Section: Figurementioning
confidence: 91%
“…It was reported that the prevalence of parental ADHD was higher in children with ADHD, 34 and children born to parents with ADHD had an increased risk of ADHD. 42 We also noted that the authors of studies with a sibling design did not show the relationship between maternal smoking and ADHD, 20,27,36 suggesting a key role for genetics in the development of ADHD. In those sibling-design studies, the authors suggested that the family context and genetic factors are similar in siblings.…”
Section: Figurementioning
confidence: 94%
See 2 more Smart Citations
“…The comparison of siblings of mothers who smoked during one pregnancy but not the other controls for many familial confounds, thus providing a far more stringent test of association than most other research designs. With this method it has been shown that smoking is systematically linked to lower birth weight in the offspring but does not appear to influence the offspring's risk for mental health problems (Gustavson et al, 2017;Kuja-Halkola, D'Onofrio, Larsson, & Lichtenstein, 2014;Lahey & D'Onofrio, 2010).…”
mentioning
confidence: 99%